Engineering of organic dyes for highly efficient p-type dye-sensitized solar cells. (January 2016) - Wu, Fei; Zhu, Linna; Zhao, Shangbi; Song, Qunliang; Yang, Chuluo
Abstract: Four organic dyes, namely T3, T3H, T4 and T4H, are designed and synthesized for p-type photocathodes. Different from the widely explored method of extending conjugation between donor and acceptor, in these dyes, the distance between donor and the semiconductor surface is elongated by three or four alkylated thiophene units. Dicyanovinyl and 1, 3-diethyl-2-thiobarbituric acid are introduced as the acceptor units, respectively. It turns out that the increased oligothiophene units between triphenylamine and carboxylate enhances the light harvesting efficiency. Moreover, the thiobarbituric acid offers much broader and stronger absorption reaching the NIR region, thus leading to higher photocurrents in T4H. As a result, dye T4H shows the highest power conversion efficiency of 0.317%, with photocurrent up to 6.735 mA/cm 2 using the I − /I3 − electrolyte. Notably, the high photocurrent obtained is close to the highest value reported to date for p-type dye-sensitized solar cells (7.57 mA/cm 2 ). Graphical abstract: Highlights: Dyes with different spacer length and acceptor groups are synthesized. The spacer increases the distance from donor group to the semiconductor surface. Thiobarbituric acid led to broader and stronger absorption in NIR region. High photocurrent up to 6.735 mA/cm 2 was achieved.